Governing Commercial Access to Health Data for Public Benefit: Charity Law Solutions. (19th August 2019) - Bell, Jessica L
Abstract: There is a growing body of evidence that supports the view that research participants and the public are concerned about commercial access to health data. Evidence also suggests that attitudes are ameliorated when charity organisations are involved and where research promises to deliver 'public benefit'. To a significant extent, therefore, mechanisms that ensure the public benefit are key to sustaining public and participant support for research access to health data. As a regime founded on the concept of public benefit, charity law provides regulatory and governance mechanisms through which the public benefit of a charity is protected and promoted. This article examines the merits of charity law mechanisms and analyses their significance for governance of commercial access to health data for public benefit, using UK Biobank Ltd, a charitable company limited by guarantee, as an example. The article critically analyses three charity law mechanisms that operate to ensure that an organization providing access to data meets its public benefit requirements: charitable purposes; members' and directors' powers and duties; and accountability via the oversight powers of the Charity Commission and charity proceedings in court. The article concludes that there is potential for the charity model to be the benchmark for governing commercial access to health data for public benefit research, but notes the limitations of the model and recommends the appointment of independent data governance committees to further bolster the charity law framework.